Using Microsoft Dynamics AX 2012 Updated for Version R3 - Luszczak, Andreas (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2015)
Precise descriptions and instructions enable users, students and consultants to understand Microsoft Dynamics AX 2012 rapidly. Microsoft offers Dynamics AX as its premium ERP solution, supporting large and mid-sized organizations with a complete business management solution which is easy to use. Going through a simple but comprehensive case study - the sample company 'Anso Technologies Inc.' - this book provides the required knowledge to handle all basic business processes in Dynamics AX. Exercises are there to train the processes and functionality, also making this book a good choice for self-study. Contents Basics and Technology - Navigation and User Interface - Supply Chain Management - Trade and Logistics - Warehouse and Transportation - Manufacturing - Financial Management Target Group IT executives IT professionals and consultants for business management solutions New and current users of Dynamics AX Students of information technology, business administration and similar disciplines Author Dr. Andreas Luszczak is project manager and consultant, responsible for the implementation of Microsoft Dynamics AX in numerous projects. He has been teaching Dynamics AX at renowned universities in Austria. In addition to Dynamics AX, he has years of experiences with the implementation of other business solutions (Microsoft Dynamics NAV/Navision and others) working as consultant and as IT manager/CIO in the industry.